Pengaruh Mental Accounting, Teknologi Informasi Dan Kualitas Sumber Daya Manusia Terhadap Kinerja UMKM Kecamatan Binawidya Pekanbaru - Rizky Dwi Anggraini; Wira Rasamashar; Rama Gita Suci (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The purpose of this study is to ascertain how mental accounting, information technology, and the quality of human resources affect the performance of small and medium-sized enterprises (SMEs) in the Binawidya Pekanbaru District. This study's sample consists of 175 UMKM MSMEs in the Bianwidya subdistrict. 152 samples from 175 data samples that can be processed. Quantitative research is the type of study in question.The information investigation technique utilized is different direct examination, the information is handled utilizing programming SPSS rendition 26. Mental accounting, information technology, and the quality of human resources all have a positive and significant impact on the performance of MSMEs in the subdistrict of Binawidya, according to the findings of this study.